Measurements of Wake Concentration from the Continuous Release of a Dense Fluid Upstream of a Cubic Obstacle - Romana Akhter; Nigel B. Kaye (Fluids)
Results are presented from a series of small-scale laboratory experiments designed to model dense gas dispersion around an isolated cuboid building. Experiments were conducted for a broad range of flow Richardson numbers and source discharge rates, and the concentration field in the wake of the building was measured using light-induced fluorescence (LIF). Results show that, for low Richardson numbers, the concentration of dense fluid in the wake decreases slightly with distance above the ground. However, for Richardson numbers above <semantics>Ri≈3</semantics>, the vertical variation is qualitatively different, as a dense lower layer forms in the wake and the concentration above the layer is much lower than for the lower Ri experiments. For these higher Richardson number flows, the primary mechanism by which dense fluid is flushed from the building wake is by the wake flow skimming dense fluid from the top of the lower layer and then moving it upstream toward the building’s leeward face. It is then transported up the leeward face of the building and then downstream. The results also generally show that, as the release rate of dense fluid increases, the density and thickness of the lower layer increases. The LIF measurements and a series of visualization experiments highlight the complex interaction of a dense fluid discharge with the wake structure behind a building.